PENGARUH PELARUT (ETIL BENZENA), PERBANDINGAN STYRENE BUTADIENE RUBBER (SBR) TERHADAP STIREN, DAN JUMLAH INISIATOR (BPO) PADA PEMBUATAN HIGH IMPACT POLYSTYRENE (HIPS) - Wahyuni, Dwi (Indonesian Journal of Aerospace, 2004)
High impact polystyrene (HIPS) is the widely used material now, and also for the aerospace material as a communication instrument system and an electrical insulation. In order to produce HIPS, there are a view method which can be executed. In this case, the research is executed by the copolymerization processes of styrene butadiene rubber (SBR) solution in styrene. Variables which influence to the result properties (HIPS) are the SBR to styrene ratio, the solvent (ethyl benzene), the benzoyl peroxide initiator (BPO). The properties of the product are tensile strength, impact strength, softening point, melting point and the hardness. The result showed that the properties of the HIPS product was near of the HIPS high heat. The optimal processes condition was the solvent to the styrene monomer ratio was 0.05492, the SBR to the styrene ratio was 0.1236 and the BPO to the styrene ratio was 0,0003. The properties of the HIPS product were: the impact strength was (519-1215) N per cm, the tensil strength not more than was 106 N per cm, the elongation was (36-54) percent and the hardness was (65-69) shore A. This properties achieved at the mixing polymerization processes 4 scale in 11-12 hours, the early mixing at 4 scale 1 hours, the cutting chain 2 drops.